Determinants of social expenditure in OECD countries - Florian Haelg; Niklas Potrafke; Jan-Egbert Sturm (ETH Zurich, KOF Swiss Economic Institute, 2020)
We portray determinants of social expenditure in OECD countries. Many theories have been proposed to describe why social expenditure has increased in industrialized countries. Determinants include globalization, political-?institutional variables such as government ideology and electoral motives, demographic change and economic variables such as unemployment. Scholars have used social expenditure as the dependent variable in many empirical studies. We employ extreme bounds analysis to examine robust predictors of social expenditure. Our sample includes 31 OECD countries over the period 1980-?2016. The results suggest that budget deficits, trade globalization and fractionalization of the party system were negatively associated with social expenditure. Aging, unemployment, social globalization, coalition governments and public debt were positively associated with social expenditure. Moreover, social expenditure increased under left-?wing governments when de facto trade globalization was pronounced. Results based on Bayesian model averaging corroborate the relationships found between banking crisis, de facto trade globalization, social globalization, legislative fractionalization, coalition governments, public debt and budget deficits on the one hand and social expenditure on the other. We conclude that policymakers in individual countries use domestic measures to design social policies - globalization, aging, and business cycles notwithstanding.
hdl:20.500.11850/407604
Keywords: F57; I38; O11; O57; C23; 330; social expenditure; OECD countries; extreme bounds analysis; Bayesian model averaging